EFEKTIFITAS PEMBERIAN KOMPRES KOMBINASI HANGAT DAN DINGIN TERHADAP PERUBAHAN INTENSITAS NYERIÂ RHEUMATOID ARTHRITIS PADA LANSIA DI DUSUN JANTI Â DESA JANTI KECAMATAN JOGOROTO KABUPATEN JOMBANG - Achwandi, Moch. (JURNAL KEPERAWATAN SEHAT, 2015)
Rheumatoid arthritis in the elderly can lead to an increase in the intensity of pain caused by inflammation. One non-pharmacologic therapies are used to reduce the intensity of pain using a combination of warm and cold compresses. Warm compresses and cold compresses can be trusted increase the pain threshold. The purpose of this study was to prove whether or not the intensity changes Rheumatoid Arthritis Pain in the Elderly. The method used is a pre-experimental design with one group pretest-posttest design. The sample in this study was the total population of elderly with rheumatoid arthritis were taken with total sampling with 20 respondents. The instrument used in this study is a fixed procedure granting of warm and cold compresses. Results presented descriptively and presented in the form of the frequency distribution table. Known pain scale respondents before and after treatment showed a decrease given pain scale. It shows, there Rheumatoid Arthritis Pain Intensity Changes in the Elderly by Providing Combination Warm and cold compresses. Said gate control theory of cutaneous stimulation warm and cold compresses nerve fibers activate the sensor A-beta big where when stimulus tactile (feeling) that dominates in the gelatinous substance to be met so that the pain gate closes the gate synapses transmission / unobstructed pain stimulus resulted in a decrease in pain intensity. Based on the above results, it is expected the combination of warm and cold compresses can be used by respondent to reduce the intensity of joint pain in addition to pharmacological therapy.Keywords: warm and cold compresses, rheumatoid arthritis pain